Contrasting effects of genotype and root size on the fungal and bacterial communities associated with apple rootstocks. Issue 1 (18th January 2022) - Liu, Jia; Abdelfattah, Ahmed; Wasserman, Birgit; Wisniewski, Michael; Droby, Samir; Fazio, Gennaro; Mazzola, Mark; Wu, Xuehong
Abstract: The endophytic microbiome of plants is believed to have a significant impact on its physiology and disease resistance, however, the role of host genotype in determining the composition of the endophytic microbiome of apple root systems remains an open question that has important implications for defining breeding objectives. In the current study, the bacterial and fungal microbiota associated with four different apple rootstocks planted in April, 2018 in the same soil environment and harvested in May, 2019 were evaluated to determine the role of genotype on the composition of both the bacterial and fungal communities. Results demonstrated a clear impact of genotype and root size on microbial composition and diversity. The fungal community was more affected by plant genotype whereas the bacterial community was shaped by root size. Fungal and bacterial abundance was equal between different-sized roots however, significantly higher microbial counts were detected in rhizosphere samples compared to root endosphere samples. This study provides information that can be used to develop a comprehensive and readily applicable understanding of the impact of genotype and environmental factors on the establishment of plant microbiome, as well as its potential function and impact on host physiology.